A hierarchical carbon nitride tube with oxygen doping and carbon defects promotes solar-to-hydrogen conversion. Issue 6 (22nd January 2020) - Sun, Zongzhao; Wang, Wu; Chen, Qianwen; Pu, Yayun; He, Heng; Zhuang, Weiman; He, Jiaqing; Huang, Limin
Abstract : Hierarchical pipe-in-pipe carbon nitride with oxygen doping and carbon defects synergistically promotes solar-to-hydrogen conversion. Abstract : Micro-nanostructures, element doping and structural defects are three pivotal factors that determine the photocatalytic activity of the graphitic carbon nitride polymer. Green and additive-free construction of the above three-in-one carbon nitride (CN) based materials is extremely challenging. Herein the target hierarchical carbon nitride tube with a pipe-in-pipe double-layer and porous coral-like architecture as well as oxygen doping and carbon defects is successfully obtained via a self-templating method. Melamine is the only precursor in the whole process, and there are no harmful solvents or cross-linking agents used for self-assembly with cyanuric acid, which comes from melamine under hydrothermal treatment. Surpassing the simple hollow carbon nitride tube, this hierarchical hollow structure, which is clearly visualized by 3D electron tomography, offers more contact sites and creates new heterogeneous catalytic interfaces synergistically. Hence, the as-prepared photocatalyst achieves a satisfactory hydrogen yield, ascribed to the large surface area, short charge transfer distance, light scattering, fast mass transfer and suitable bandgap with midgap states. This eco-friendly method provides a new opportunity for designing novel micro-nanostructures with desirable performance in solar-to-chemical energy conversion.